Key Role of the Membrane Trafficking of Nav1.5 Channel Protein in Antidepressant-Induced Brugada Syndrome - Chen, Xi; Zhu, Chao; Zhou, Hao; Zhang, Yu; Cai, Zhongqi; Wu, Honglin; Ren, Xiaomeng; Gao, Lei; Zhang, Jiancheng; Li, Yang (Frontiers in Physiology, 2018)
Anti-depressant treatment has been found to be associated with the development of Brugada syndrome (BrS) through poorly defined mechanisms. Herein, this study aimed to explore the molecular basis for amitriptyline-induced BrS. The effects of long-term treatments of amitriptyline on Nav1.5 were investigated using neonatal rat ventricular myocytes. The electrophysiological properties, expression and distribution of Nav1.5 were studied using the patch clamp, Western blot and confocal laser microscopy assays. Interactions between Nav1.5 and its interacting proteins, including ankyrin-G and dystrophin, were evaluated by co-immunoprecipitation. A larger decrease in the peak INa occurred after long-term treatments to amitriptyline (56.64%) than after acute exposure to amitriptyline (28%). Slow recovery from inactivation of Nav1.5 was observed after acute or long-term treatments to amitriptyline. The expression of Nav1.5 on the cell membrane showed a larger decrease by long-term treatments to amitriptyline than by acute exposure to amitriptyline. After long-term treatments to amitriptyline, we observed reduced Nav1.5 proteins on the cell membrane and the disrupted co-localization of Nav1.5 and ankyrin-G or dystrophin. Co-immunoprecipitation experiments further testified that the combination of Nav1.5 and ankyrin-G or dystrophin was severely weakened after long-term treatments to amitriptyline, implying the failed interaction between Nav1.5 and ankyrin-G or dystrophin. Our data suggest that the long-term effect of amitriptyline serves as an important contribution to BrS induced by amitriptyline. The mechanisms of BrS induced by amitriptyline were related to Nav1.5 trafficking and could be explained by the disrupted interaction of ankyrin-G, dystrophin and Nav1.5.